1997
DOI: 10.1023/a:1008209429204
|View full text |Cite
|
Sign up to set email alerts
|

Phase I–II study of vinorelbine in combination with 5-fluorouracil and folinic acid as first-line chemotherapy in metastatic breast cancer: A regimen with a low subjective toxic burden

Abstract: This effective combination chemotherapy of vinorelbine, 5-fluorouracil and folinic acid is comparable to other first-line regimens in terms of efficacy, and is subjectively well tolerated, thus deserving a test in randomized trials in the advanced and adjuvant settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
9
0
1

Year Published

2005
2005
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 20 publications
4
9
0
1
Order By: Relevance
“…Although survival is not a major end point for evaluation of efficacy in phase II trials, the median overall survival of 25 months in this study was favourably within the range of other previously reported major protocols of anthracycline-based regimens (Ross et al, 1985;Clavel and Catimel, 1993;Jassem et al, 2001;Biganzoli et al, 2002;Sledge et al, 2003), taxane-based regimens (Jassem et al, 2001;Biganzoli et al, 2002;Sledge et al, 2003), and vinorelbinebased regimens (Dieras et al, 1996a;Nole et al, 1997;Norris et al, 2000).…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Although survival is not a major end point for evaluation of efficacy in phase II trials, the median overall survival of 25 months in this study was favourably within the range of other previously reported major protocols of anthracycline-based regimens (Ross et al, 1985;Clavel and Catimel, 1993;Jassem et al, 2001;Biganzoli et al, 2002;Sledge et al, 2003), taxane-based regimens (Jassem et al, 2001;Biganzoli et al, 2002;Sledge et al, 2003), and vinorelbinebased regimens (Dieras et al, 1996a;Nole et al, 1997;Norris et al, 2000).…”
Section: Discussionsupporting
confidence: 74%
“…The overall response rate of 70.0% (95% confidence interval: 54 -84%) was within the range (40 -70%) of previously reported major protocols of anthracycline-based regimens (Ross et al, 1985;Clavel and Catimel, 1993;Jassem et al, 2001;Biganzoli et al, 2002;Sledge et al, 2003), taxane-based regimens (Jassem et al, 2001;Biganzoli et al, 2002;Sledge et al, 2003), and anthracyclineand-taxane-based regimens (Razis and Fountzilas, 2001;Sledge et al, 2003). Previously, studies from other series using vinorelbine and different administration schedules of 5-FU and LV have also demonstrated a good efficacy in breast cancer (Dieras et al, 1996a;Nole et al, 1997). However, the 5-day loading schedule of 5-FU created significant treatment-related toxicity, which may limit its clinical use (Dieras et al, 1996a).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…La asociación de 5FU/vinorelbina tiene ventajas teóri-cas que son: mecanismos diferentes de citotoxicidad, resistencia y una baja sobreposición de sus efectos tó-xicos 17,18 . En seis estudios fase II se ha reportado la efectividad y toxicidad de esta combinación, todos ellos con dosis diferentes de fluoruracilo y vinorelbina [23][24][25][26] . En nuestro estudio, con el fin de minimizar los efectos tóxicos pero sin restar efectividad, redujimos la frecuencia de vinorelbina a cada 21 días y se compensó con 5FU en infusión continua.…”
Section: Introductionunclassified